HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLAH YANG DI HOSPITALISASI DI RS SYECKH YUSUF GOWA - Ahmad Mushawwir; Haikal Alpin; Eka Andryanto (Stikes Graha Edukasi Makassar, 2019)
Family support is the attitude, action, appreciation, encouragement and enthusiasm given by the family to children who are hospitalized. Anxiety is a person's emotional turmoil related to something outside himself and the self-mechanisms used in dealing with problems. The purpose of this study was to determine the relationship between family support and anxiety levels in children who were hospitalized at pre-school age at Syech Yusuf Gowa Hospital in 2019. In this study, the research design used was analytic with a cross-sectional approach, samples were taken using purposive sampling, data analysis through a computer program with an error rate of 0.05. The number of samples in this study were 30 respondents and used questionnaires and interview sheets. The chi-square test was conducted to assess the relationship between the independent variable (family support) and the dependent variable (anxiety). The results of the chi-Square test showed that there was a relationship between family support and the level of anxiety in preschoolers with a value of p=0.017 (p<0.05). From the results of the research above, it can be concluded that a good family support relationship can influence anxiety responses towards children, especially in the process of hospitalization. By knowing how important the family support relationship is for children who are hospitalized at Sheikh Yusuf Gowa Hospital, family support for children is very important because. has a significant relationship so that it can affect the level of anxiety in children who are hospitalized at Rs Sheikh Yusuf Gowa